ACUPUNCTURE AND NURSING CARE TO THE OBESE PERSON - Luciara Fabiane Sebold; Vera Radunz; Patrícia Kuerten Rocha (Universidade Federal do Paraná, 2006)
This study is an experienced account with a qualitative approach. Its objective is to reflect upon the efficiency of the relationship between nursing care and acupuncture in order to treat the obese. Data were collected through a previously elaborated protocol, which contained both objective and subjective questions about the patient's physical and emotional states. At the same time, the knowledge of traditional Chinese medicine was applied through the use of acupuncture. It became clear during the patient's session that she followed the suggested treatment, and usually referred to her emotional state. Through nursing care and acupuncture, the patient's energy levels were reestablished, which led to weight loss as well as emotional balance.